Change Organizational Culture at Private Hospital Surabaya in Facing the COVID-19 Pandemic and New Normal - Abu Thoyyib; Ratna Wardani; Estiningtyas Nugraheni; Yohana Rusmeitasari (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to analyze changes in organizational culture in hospitals in the face of the COVID-19 Pandemic and the New Normal. Using qualitative methods with a case study approach and data collection techniques through interviews and document review. Research informants as many as 4 people, the Chairman of the Foundation as a representative of the owner and representatives of top management as key informants, for triangulation informants represented by the Head of the Internal Control Unit and representatives of Middle Management and a document review was carried out. Data analysis used the Organizational Culture Assessment Instrument (OCAI) method. The results show that the dominant organizational culture before the Covid-19 pandemic was Clan and during the pandemic it became Hierarchy and Adhocracy became the expected culture. This finding indicates that before the pandemic the organization became a fun place like family and during the pandemic it became structured, controlled and there were procedures for each activity. The expected culture is that the organization becomes a dynamic, entrepreneurial, and innovative place. To integrate adhocracy culture into the organization, there are several things that must be done: 1). Anticipating needs, 2) Continuous improvement; 3) Finding creative solutions; 4) Creating new standards; 5) Encouraging innovation 5) Creating new opportunities/customers; 6) Dare to take risks.